Mapping frameworks and approaches to measuring the quality of transition support services for young people with intellectual and developmental disabilities - Beadle-Brown, Julie; Šiška, Jan; Káňová, Šárka (Frontiers in Rehabilitation Sciences, 2023)
Transition to adulthood for young people with intellectual disabilities and developmental disabilities (IDD) has been given significant attention in research, policy development and practice. The aim of this paper was to explore how a recently developed theoretical outcomes-based framework for measuring the quality of services for people with disabilities could potentially be useful in conceptualizing and supporting successful transition to adulthood. The theoretical discussion draws on both the scoping review and template analysis that was used to develop the Service Quality Framework and on a separate study synthesizing expert completed country templates and literature review which included models of and research on successful transition to adulthood. Synthesis identified that using a quality of life outcomes focused framework of Service Quality could be mapped onto and extend current thinking on what is seen as successful transition to adulthood by putting the focus on successful transition as people with IDD moving towards having similar opportunities and quality of life as other adults without disabilities living in the same community/society. Implications of a more wide-ranging definition and holistic view for both practice and future research are discussed.